Assessing doming mitigation strategies for enhanced inspection of masonry retaining walls with SfM as a cost-effective 3D imaging solution - Wondolowski, Maxwell; Hain, Alexandra; Motaref, Sarira; Grilliot, Michael (Frontiers in Built Environment, 2025)
Masonry retaining walls are prone to bulging and leaning failures which require high accuracy measurements to monitor. Current assessments of retaining walls rely on qualitative visual inspections that inform overall condition ratings. The site and surface conditions of retaining walls make them challenging objects to 3D image with SfM. SfM is prone to radial distortion, doming, which has resulted in research into mitigation strategies. This study assesses the best practices for implementing Uncrewed Aerial Systems (UAS) to conduct Structure from Motion Photogrammetry (SfM) on masonry retaining walls as a more objective, accurate, and accessible means of inspection. The efficacy of doming mitigation strategies when applied to masonry retaining walls was explored in the current study. This was carried out through the duplicate imaging of two sample retaining walls with terrestrial laser scanning (TLS) and SfM. The TLS generated 3D models were used as baselines to compare the trial SfM generated 3D models with CloudCompare. SfM models not initially exhibiting doming displayed an average of 5.8 mm (0.23 in) root mean square error (RMSE) when compared to TLS baselines. The errors in SfM models that exhibited doming were improved with the addition of ground control points, resulting in a 46% reduction in error. Findings and the best practices for SfM image networks and ground control point inclusion for two retaining walls are provided based on results of this research. The benefits and inherent limitations of SfM as used for retaining wall 3D imaging to contribute to the growing applications of SfM in infrastructure inspections are discussed.